Hubungan Karakteristik Mahasiswa Dengan Kecenderungan Perilaku Cyberbullying - Mayzar Briliana Widiya Ningrum; Suci Ratna Estria (Jurnal Keperawatan Muhammadiyah, 2020)
The development of Information Technology (IT) in the community is very rapid and able to change human lifestyles to meet information needs. Nowadays, information can spread very quickly and be difficult to control which causes an increase in the use of IT, especially social media. This has led to bullying behavior through  social media (cyberbullying), especially among adolescents who have a negative impact and influence on behavior such as the personality and self-control. Objective:To determine the correlation between students' characteristics (personality and self-control) and the tendency of cyberbullying behavior in the Faculty of Health Sciences UMP.Method: This is a quantitative correlational study with a cross-sectional approach. The population is 43 students who were the cyberbullying perpetrators at the Faculty of Health Sciences UMP. The sampling technique was total sampling; it selected 43 students. The researchers used univariate and bivariate analysis.Results: It shows that more respondents are women or 34 people (79.1%) than men who are only 9 people (20.9%). The respondents who have introverted personality types are 19 people (44.2%) and 24 people (55.8%) are extroverted. The ability of self-control is mostly moderate, it shows 18 people are moderate (41.9%), 10 people (23.3%) are very low and 1 person (2.3%) is very high. Based on the Sig. (2-tailed) between personality type (X1) and cyberbullying behavior (Y) it showed a score of 0.035 0.05, and between quality control (X2) and cyberbullying behavior (Y) the score of 0.009 0.05 was obtained, so that it could be concluded that there is a correlation between the characteristics of students and the tendency of cyberbullying behavior.Conclusion: Most of the students were in extrovert personality types (55%) and the quality of self-control was in the moderate category (41.9%).